Development of a Differentiated Art Painting E-Module Integrating Environmental Education through Arts for Vocational Students - Titian Cahya; Sutji Muljani; Burhan Eko Purwanto (FKIP - Universitas Riau, 2026)
This study aims to develop a differentiated art painting e-module integrating environmental education through arts for vocational students. Conventional art painting instruction in vocational schools often applies uniform learning approaches and lacks environmental context, resulting in low student engagement and limited learning relevance. This research employed a research and development method to design, develop, and evaluate an e-module that accommodates students’ diverse learning characteristics while embedding environmental education concepts through artistic activities. The development process included needs analysis, product design, e-module development, expert review, and limited field testing. Data were collected using validation sheets, questionnaires, and learning outcome assessments. The results indicate that the developed e-module is pedagogically appropriate, visually engaging, and relevant to vocational students’ learning needs. The integration of differentiated learning and environmental education through arts supports students’ understanding of art concepts while fostering environmental awareness. The findings suggest that the developed e-module can be used as an alternative instructional resource to support meaningful and contextual art painting learning in vocational education. Further implementation on a wider scale is recommended to examine its effectiveness across different vocational school contexts.